Irrigation effects on peaches, apples and pears in commercial orchards - García Petillo, M.; Puppo, L.; Romero, G.; Baccino, G. (Agrociencia Uruguay, 2003)
This paper summarises the information generated after six years of drip irrigation research on adult peach, pear and apple trees in commercial orchards in the south of Uruguay. During the first three years, different doses and moments of irrigation were evaluated. Then, experiments were modified, and only irrigation was evaluated. In peach trees cv. “Rey del Monte” a slight trend to increase yield with irrigation was detected, mainly due to a larger fruit size. Furthermore, an earlier harvest was obtained. In apple trees cv. “Red Spur” irrigation increased yield 10%. In pear trees cv. “Williams” irrigation increased yield 38% in average for the six years, with an increase of fruit size of 21 grams. In this crop irrigation improved 64% the yield of greater commercial value fruits (larger than 110g), being this improvement of 147% in the season which more water was applied. Deficiencies were detected on the water volume applied, due to limited water sources, mistakenly designed irrigation equipment and/or lack of knowledge in irrigation management among the farmers.